PENGARUH NILAI TAMBAH EKONOMI DAN SYSTEMATIC RISK TERHADAP STOCK PRICE - Moh Abdurrosyid; Sabila Nuraini (AKRUAL : Jurnal Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of Economic Value Added (EVA) and Systematic Risk on Stock Prices in Pharmaceutical Subsector Companies listed on the Indonesia Stock Exchange for the period 2013-2021. The population in this study was obtained by 11 companies using purposive sampling method on pharmaceutical subsector companies listed on the Indonesia Stock Exchange and based on predetermined criteria, a sample of 7 pharmaceutical subsector companies was obtained. The analytical method used in this study is a quantitative method, with panel data regression analysis which is processed with the Eviews 9 application program. Based on the results of the t test, it can be concluded that partially the Economic Value Added (EVA) variable has a significant positive effect on stock prices, while the Systematic Risk variable has a significant negative effect on stock prices. Based on the results of the F test, it is concluded that there is a simultaneous (together) significant effect between the variables of Economic Value Added (EVA) and Systematic Risk on Stock Prices.